PENGARUH WORKPLACE SPIRITUALITY DAN ETHICAL LEADERSHIP TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN EMPLOYEE WELLBEING SEBAGAI VARIABEL PEMEDIASI - Ricky Kristiawan; Martinus Parnawa Putranta (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2024)
This study aims to provide an empirical explanation of the influence of spirituality in the workplace and ethical leadership on organizational citizenship behavior (OCB) with employee wellbeing as a mediating variable with the object of research employees of PT. Indo Muro Kencana in Central Kalimantan. The questionnaire was distributed online with a total of 296 respondents using a sampling technique, namely quota sampling. The collected data was then analyzed using the SEM-PLS approach (SmartPLS 3.29). The results showed that workplace spirituality has a positive and significant effect on employee wellbeing. Ethical leadership has a positive and significant effect on employee wellbeing. Workplace spirituality has a positive and significant effect on OCB. Ethical leadership has a positive and significant effect on OCB. Employee wellbeing has a positive and significant effect on OCB. The mediating effect of employee wellbeing between workplace spirituality on OCB. The mediating effect of employee wellbeing between ethical leadership on OCB. Keywords: workplace spirituality; ethical leadership; employee wellbeing; organizational citizenship behavior. Penelitian ini bertujuan untuk memberikan penjelasan secara empiris tentang pengaruh workplace spirituality dan ethical leadership terhadap organizational citizenship behavior (OCB) dengan employee wellbeing sebagai variabel pemediasi dengan objek studi karyawan PT. Indo Muro Kencana di Kalimantan Tengah. Penyebaran kuesioner dilakukan secara online dengan jumlah responden 296 orang dengan teknik pengambilan sampel yaitu quota sampling. Data yang sudah terkumpul kemudian dianalisis dengan pendekatan SEM-PLS (SmartPLS 3.29). Hasil penelitan menunjukkan bahwa workplace spirituality berpengaruh positif dan signifikan terhadap employee wellbeing. Ethical leadership berpengaruh positif dan signifikan terhadap employee wellbeing. Workplace spirituality berpengaruh positif dan signifikan terhadap OCB. Ethical leadership berpengaruh positif dan signifikan terhadap OCB. Employee wellbeing berpengaruh positif dan signifikan terhadap OCB. Employee wellbeing memediasi pengaruh antara workplace spirituality terhadap OCB. Employee wellbeing memediasi pengaruh antara ethical leadership terhadap OCB. Kata kunci: workplace spirituality; ethical leadership; employee wellbeing; organizational citizenship behavior.